Virtual Approach in Teaching Anglo-American Literature and Students’ Comprehension Skills - Andao, Sahera Dalimbang; Ambayon, Cristobal Millenes (American Journal of Education and Learning, 2020)
This paper worked on the use of Virtual Approach in Teaching Anglo-American Literature and Students’ Comprehension Skills. The study tested the acceptability of the instructional module and virtual materials in terms of its content, relevance and instructional quality that was validated as highly acceptable. The researchers used experimental method of research to the 33 grade 9 students of Columbio National High School and 33 for the control group, randomly selected. Findings revealed that students from the control group did not meet the expectations in their pre-test and post-test, while the experimental group performance did not meet the expectation in the pre-test and very satisfactory after the integration of Virtual Approach. These results were further explained through the use of t-test using 0.05 level of significance. It revealed that there was a significant difference between the mean gain score of control and experimental groups which mean that the experimental group improved better and learned more using virtual approach in teaching Anglo-American Literature than the use of book, board and chalk in the control group. This concluded that the use of Virtual Approach in teaching, improved students’ comprehension skills and recommended the use of Virtual Approach in teaching literature.